2021
DOI: 10.1186/s13089-021-00246-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound at the patient’s bedside for the diagnosis and prognostication of a renal colic

Abstract: Background Diagnosing a ureteral colic is sometimes difficult; however, clinicians should not fail to detect a surgical emergency. This is why diagnostic strategies depend on the imaging examinations, especially ultrasound. Prior studies have investigated the accuracy of Point of Care Ultrasound (PoCUS), but there are relatively few. This study aimed to evaluate the performance of the PoCUS in the diagnosis of renal colic. The secondary objective was to evaluate the relationship between the ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…To our knowledge, only one small, prospective, recently published study investigated the use of POCUS by EPs to directly identify obstructive ureteral stones. Bourcier et al [ 10 ] demonstrated in a group of 103 patients that, while EPs had an accuracy of POCUS of 91% for detecting urinary tract dilatation, they had only a 54% accuracy for directly detecting kidney stones. Along with study strengths, such as the methodologic design, there are a few limitations, including a relatively small population from a single small emergency unit (19,000 visits per year) as well as highly demanding criteria for POCUS performers, including a 5-day theoretical and practical training course at a certified center along with 18 months of follow-up e-learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one small, prospective, recently published study investigated the use of POCUS by EPs to directly identify obstructive ureteral stones. Bourcier et al [ 10 ] demonstrated in a group of 103 patients that, while EPs had an accuracy of POCUS of 91% for detecting urinary tract dilatation, they had only a 54% accuracy for directly detecting kidney stones. Along with study strengths, such as the methodologic design, there are a few limitations, including a relatively small population from a single small emergency unit (19,000 visits per year) as well as highly demanding criteria for POCUS performers, including a 5-day theoretical and practical training course at a certified center along with 18 months of follow-up e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a comprehensive meta-analysis showed that hydronephrosis is neither sensitive nor specific as an indicator for nephrolithiasis [ 9 ]. There is a paucity of literature on the use of POCUS by emergency physicians (EPs) to directly identify obstructive ureteral stones [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bourcier, et al (2021) 9 showed that the performance of PoCUS in detecting lithiasis, and therefore ureteral colic was as follow: accuracy, 54%; sensitivity, 43%; and specificity, 92%. Among the 85 patients diagnosed with ureteral colic, 43 had lithiasis not detected on ultrasound (14 in the bladder-ureteral junction, six in the pelvic ureter, 21 in the lumbar ureter, and two in the proximal ureter).…”
Section: Ultrasoundmentioning
confidence: 99%
“…These measures did not improve appreciably for patients with confirmed stone or signs of recent stone passage on formal imaging (sensitivity 78. 9 showed that eight patients diagnosed with renal colic had no ureteral lithiasis on CT, but had pyelocalyceal cavity dilatation. Six of them had bladder lithiasis and two had spontaneous elimination of stones between the PoCUS and CT examinations.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Thiazide diuretics are the most efficient and welltested diuretic medications, and they are successfully utilized for calcium stones. Example: Hydrochlorothiazide 20,21 . • Expulsive therapy: The expulsive method of treating kidney stones includes the use of medications to aid the naturally occurring transit of ureteral calculi.…”
Section: Non-surgical Therapiesmentioning
confidence: 99%